Pengaruh Kualitas Layanan, Brand Image dan Kepuasan Nasabah terhadap Loyalitas Nasabah di PT. Pegadaian (Persero) Cabang Pemalang : Studi Kasus pada UPC Pegadaian Ulujami - Dewi Sinta Wati; Wenti Ayu Sunarjo; Rengga Kusuma Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Service quality, brand image, customer satisfaction, customer loyalty, pawnshop Abstract. This study aims to examine the influence of service quality, brand image and customer satisfaction on customer loyalty at PT. Pemalang branch pawnshop (case study on UPC Ulujami. The population in this study is customers of PT. Ulujami branch pawnshop totaling 1250 people with a research sample of 95 people. Data collection was carried out by means of interviews and questionnaires.the analysis technique used in this researcher is multiple linear regression using the SPSS (Statistical Product and Service Solutions) version 22 program used to analyze the data. Based on the results of this study, it shows that (1) service quality has a significant effect on customer loyalty. (2) Brand image affects customer loyalty. (3) Customer satisfaction has a significant effect on customer loyalty. (4) Service quality, brand image and customer satisfaction